Cultures and organizations: Geert Hofstede's organizational cultures - Ranka Jeknić (Zbornik Radova Pravnog Fakulteta u Splitu, 2011)
The paper firstly presents some results of the cross-cultural IBM's researches, or the Geert Hofstede's model of “national culture” and dimensions of values, and cross-organizational IRIC research on organizational culture and organizational dimensions of practices. Then it analyzes the impact of “national” on the organizational culture, and presentes some conclusions about the application of Hofstede's research findings in the context of managing cultural diversity among organizations or organizational cultures, and managing cultural diversity within organizations or organizational subcultures.